2019
DOI: 10.1021/acscatal.9b04214
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Evolution of Heterogeneous Single Metal Atoms and Nanoclusters under Reaction Conditions: Which Are the Working Catalytic Sites?

Abstract: Identification of active sites in heterogeneous metal catalysts is critical for understanding the reaction mechanism at the molecular level and for designing more efficient catalysts. Because of their structural flexibility, subnanometric metal catalysts, including single atoms and clusters with a few atoms, can exhibit dynamic structural evolution when interacting with substrate molecules, making it difficult to determine the catalytically active sites. In this work, Pt catalysts containing selected types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
249
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(265 citation statements)
references
References 83 publications
12
249
0
4
Order By: Relevance
“…The stability of SACs is a critical issue for their practical applications [15][16][17]. It was reported that the presence of subnanometer clusters in SACs can affect the overall thermal stability [18][19][20][21][22][23]. Tremendous efforts are made to improve the thermal stability by enhancing the metal-support interactions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of SACs is a critical issue for their practical applications [15][16][17]. It was reported that the presence of subnanometer clusters in SACs can affect the overall thermal stability [18][19][20][21][22][23]. Tremendous efforts are made to improve the thermal stability by enhancing the metal-support interactions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…N or O), has opened up a new research frontier in the catalysis field. [1][2][3][4] Many catalytic reactions have been explored, such as methane selectively oxidation to methanol and acetic acid using Rh SSCs, [5] CO oxidation and hydrogen generation from methanol using Pt SSCs, [6][7][8] etc. The reduction of particle size to single-atom level always achieves the maximum utilization of expensive noble metals, along with enhancement of activity, stability or selectivity.…”
mentioning
confidence: 99%
“…Considering that no Pt loss was detected after calcination at high temperatures (Table S1), the possibility that the disappearance of CO adsorption might stem from volatilization of Pt can be excluded. Thus the result of no adsorption of CO should be related to the cationic nature of Pt [40] and may suggest a strong interaction between Pt and Fe. The different interactions between Pt and Fe were further studied by H 2 -TPR.…”
Section: Resultsmentioning
confidence: 99%